The Association of OTX1 rs17850223 Polymorphisms in Han Chinese Patients with Idiopathic Epilepsy. (10th March 2020) - Lv, Jin; Qu, Chunsheng; Huang, Zhenqiang; Zhu, Yingbiao; Wang, Wei; Lan, Likang
Abstract : This study is aimed at investigating the association between orthodenticle homeobox 1 ( OTX1 ) gene polymorphisms and idiopathic epilepsy in a cohort of Han Chinese patients. We carried out a case-control study on 147 patients with idiopathic epilepsy and 150 healthy controls. Genomic DNA was isolated from 1 ml of ethylene diamine tetraacetic acid (EDTA)-treated blood. The OTX1 coding sequence was divided into three parts and amplified using PCR, and the products were genotyped using the Sanger sequencing method. All OTX1 coding sequences were conserved except for rs17850223 located on the fifth exon. The frequency of the CC, CG, and GG genotypes showed no statistical differences between the idiopathic epileptic patients and the controls. The rs17850223 G allele distribution was also similar between the idiopathic epileptic patients and the controls. Interestingly, the frequency of the GG genotype was significantly higher in the patients with generalized seizures compared with that of the controls (12.2% vs. 2%, p = 0.012 ), and a greater distribution of the rs17850223 G allele was also seen in the patients with generalized seizures compared with controls (18.3% vs. 10%, p = 0.049 ). rs17850223 might play a critical role in Chinese idiopathic epileptic patients with generalized seizure activity.